2016
DOI: 10.1007/s00277-016-2628-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc levels in patients with iron deficiency anemia and its association with symptoms of iron deficiency anemia

Abstract: Iron deficiency anemia (IDA) is a major public health problem especially in underdeveloped and developing countries. Zinc is the co-factor of several enzymes and plays a role in iron metabolism, so zinc deficiency is associated with IDA. In this study, it was aimed to investigate the relationship of symptoms of IDA and zinc deficiency in adult IDA patients. The study included 43 IDA patients and 43 healthy control subjects. All patients were asked to provide a detailed history and were subjected to a physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 19 publications
5
31
0
4
Order By: Relevance
“…Kelkitli et al suggested a mediator role for zinc in iron metabolism in anemia pathogenesis. 26 The aforementioned studies and the present results indicate that the etiopathogenesis of anemia in zinc deficiency is still unclear. The proportions of the contribution of these minerals to the development of anemia are also unclear.…”
Section: Discussionmentioning
confidence: 61%
“…Kelkitli et al suggested a mediator role for zinc in iron metabolism in anemia pathogenesis. 26 The aforementioned studies and the present results indicate that the etiopathogenesis of anemia in zinc deficiency is still unclear. The proportions of the contribution of these minerals to the development of anemia are also unclear.…”
Section: Discussionmentioning
confidence: 61%
“…RDW indicates heterogeneity and equivalent of anisocytosis of red blood cell. It was documented that high levels of RDW predicts elevated red blood cell destruction in iron, folate, and vitamin B12 deficiency [19][20][21]. Eventually, different-sized erythrocytes may be expressed and elevated RDW may result in increased RPR.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Bains et al [5], Zn deficiency was detected in 17.9% of children aged 6 months-5 years, and rates of low Fe and ferritin level were 84.6% and 71.8% among children with Zn deficiency, respectively. In the studies of Tural et al [8] and Kelkitli et al [9] from Turkey, Zn deficiency has been frequently detected in patients with Fe deficiency. In the study by Erdoğan et al [10], serum Zn level was markedly lower in patients with Fe deficiency anemia than in controls.…”
Section: Discussionmentioning
confidence: 99%